Eksplorasi Model Unified Theory Of Acceptance And Use Of Technology Sebagai Pemediasi Dan Dampaknya Terhadap Minat Dan Perilaku Dalam Menggunakan Livin' By Mandiri - Sjahruddin, Herman; Akbar, Ade Putra; Alhayra, Abdul Rauf; Saputra, Ade Cahyaprandy; Ramadhani, Andi Nazalia; Jumsiani, Jumsiani (Politeknik Negeri Ambon, 2023)
This research is motivated by the continued progress of information technology. The sophistication of information technology has brought various changes to human life. One of the changes caused by technology is in the field/activity of easier transactions. Technology shifts transaction activities that are usually carried out traditionally (via ATM centers) to activities or transaction processes that can be carried out in a sophisticated and practical way (without visiting an ATM center). Livin' by Mandiri is a mobile banking application from Bank Mandiri that helps customers manage their finances easily. Apart from that, Electronic Commerce or e-commerce is all buying and selling activities or transactions carried out using electronic media (the internet). This research aims to determine the factors that influence interest and behavior in using the Livin' by Mandiri application as measured by variables in the UTAUT 2 model. This quantitative research uses a survey method with a total of 149 respondents using the Livin' by Mandiri application. Samples were taken using a purposive sampling technique. Data The analysis technique used is the SEM-PLS method, and the data is processed using SMART PLS 3.0 software. The research results show that the factors that have a significant influence on the behavior of using the Livin' by Mandiri application are behavioral influence, facilitating conditions, and social influence. Then the significant influence on behavioral interest in using the Livin' by Mandiri application is significantly influenced by Facilitating Conditions and Social Influence. Keywords: Behavioral Interest, Usage Behavior, UTAUT, UTAUT 2